Pengaruh Prestasi Kerja Dan Senioritas Terhadap Promosi Jabatan - Ratih Hadiantini; Yuliana Sylviani; Ayu Nike Retnowati (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2019)
Based on the phenomenon at the company PT. Pan Asia Jaya Abadi, which has a decrease in promotions, this is due to a lack of employee performance so that it can affect promotions. Where the current promotion system is based on employee performance and seniority, while employees in the garment unit management section of PT Pan Asia Jaya Abadi have more seniority but in poor work performance resulting in less than optimal employee performance. This study aims to determine the description of work performance and seniority on promotions and the magnitude of the influence. The method used in this research is descriptive method and verification method with a quantitative approach. The population in this study is the management of PT Pan Asia Jaya Abadi garment unit, with a total sample of 53 people with saturated sampling technique. Based on the results of the study, it is known that work performance has an effect of 61.4% on promotions, while seniority has an effect of 33.8% on promotions, simultaneously work performance and seniority have an effect of 80.6% on promotions.